The Comparison of Solar Energy Gaining Effectiveness between Flat Plate Collectors and Evacuated Tube Collectors with Heat Pipe: Case Study - Piotr Olczak; Dominika Matuszewska; Jadwiga Zabagło (Energies, 2020)
In Poland, various solar collector systems are used; among them, the most popular are flat plate collectors (FPCs) and evacuated tube collectors (ETCs). The work presents two installations located at a distance of 80 km apart, working in similar external conditions. One of them contains 120 flat plate collectors and works for the preparation of hot water in a swimming pool building; the second one consists of 32 evacuated tube collectors with a heat pipe and supports the preparation of domestic hot water for a multi-family house. During the comparison of the two quite large solar installations, it was confirmed that the use of evacuated tube solar collectors shows a much better solar energy productivity than flat plate collectors for the absorber area. Higher heat solar gains (by 7.9%) were also observed in the case of the gross collector area. The advantages of evacuated tube collectors are observed mainly during colder periods, which allows for a steadier thermal energy production.